A new ternary carbide Dy2Mn2−xC5 (x=0.6): Preparation, crystal structure, and physical properties. (April 2015) - Levytskyy, V.; Babizhetskyy, V.; Magun, A.; Heinrich, P.; Salamakha, L.; Bauer, E.; Michor, H.; Kotur, B.
Abstract: The crystal structure, magnetic and electrical transport properties of the new ternary compound Dy2 Mn2− x C5 ( x =0.6) have been investigated. According to X-ray powder diffraction the carbide crystallizes in its own structure type, space group I 4/ mmm, a =3.6421(2), c =15.7713(9) Å, R B =0.062, R p =0.134. The crystal structure contains isolated carbon atoms and C2 dimers in square-bipyramidal holes and distorted bicapped square anti-prisms, respectively. Manganese atomic positions in the structure were found to be not fully occupied. Physical properties were studied in the temperature range down to 0.4 K. The electrical resistivity of Dy2 Mn2− x C5 ( x =0.6) reveals its basically metallic nature with a positive temperature coefficient above about 30 K. A resistive anomaly at around 20 K indicates the appearance of an antiferromagnetic superzone boundary gap at low temperatures. A phase transition towards long range antiferromagnetic magnetic ordering below 19 K is further revealed by heat capacity and ac susceptibility data. Magnetization data refer to a non-trivial nature of the magnetic ground state which may be caused by the intrinsic structural disorder associated with random vacancies at the Mn site. Graphical abstract: Highlights: Crystal structure of the new ternary carbide Dy2 Mn2− x C5 ( x =0.6) was determined. The electrical resistivity of Dy2 Mn2− x C5 ( x =0.6) has a metallic nature. Compound reveals a complex nature of the antiferromagnetic ground state.